A Novel Multi-Port Containment System for Laparoscopic Power Morcellation to Prevent Tumoral Spread: A Retrospective Cohort Study - Wang, Wenhui; Liang, Haiyan; Zhao, Fang; Yu, Huan; Rong, Chunhong; Feng, Weiwei; Chen, Qingyun; Yang, Yanjun; Li, Qian; Feng, Dingqing; Dong, Yuxiao; Xue, Ming; et al. (Frontiers in Surgery, 2022)
OBJECTIVE: To report a novel multi-port containment (NMC) system for laparoscopic power morcellation to prevent tumoral spread and evaluate its safety, validity, and feasibility. METHODS: The retrospective study included women who underwent laparoscopic myomectomy (LM) (the NMC system was used for the study group, n=193; the control group underwent unprotected LM, n=1753) between January 2014 and August 2020 at a single academic institution. RESULTS: After 1:1 propensity score matching, 193 cases in each group showed no significant differences in baseline characteristics. Two bag damages were detected before the morcellation, and the NMC systems were replaced. There was no significant difference between the two groups in terms of complications, total operative time, estimated blood loss, or postoperative hospitalization duration. In the study group, all operations were completed, and no system rupture or leakage was observed. The median follow-up period was 21 months and 54 months in the study and control groups, respectively. There was no peritoneal tissue spread in the study group; three patients (3/5, 0.6%) had malignant, and six patients (6/1753, 0.3%) had benign peritoneal tissue spread in the control group. CONCLUSION: The NMC system for laparoscopic power morcellation is a valid, safe, and feasible technique to avoid tumor spread.